The sacred in a secular age: Toward revision in the scientific study of religion - Hammond, Phillip E. (Berkeley University of California Press, 1985)
Sacred in a Secular Age, edited by Phillip E. Hammond, brings together leading scholars to reassess one of the most enduring assumptions in the sociology of religion: the secularization thesis. Long taken as conventional wisdom, the thesis posits an inexorable decline of the sacred as societies modernize. Yet the persistence$1 (Band even resurgence$1 (Bof religion in new movements, conservative traditions, and political struggles around the world challenges the adequacy of this model.s